1989
DOI: 10.1016/s0741-5214(89)70011-2
|View full text |Cite
|
Sign up to set email alerts
|

Vascular prosthetic infection with Staphylococcus epidermidis: Experimental study of pathogenesis and therapy

Abstract: To determine whether a slime-producing strain of Staphylococcus epUlermUlis was capable of producing acute infection of a prosthetic vascular graft, 5 cm segments of knitted Dacron were implanted in the infrarenal aortic position ofdogs in three groups ofanimals. 'These included a control group (no graft contaminati~n), a contaminated group that received a graft soaked in an S. epidermidis solution (untreated group), and a contaminated group in which pe~operative antibiotics (three doses of ce(amandole, 100 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This is in contrast to the established infrarenal aortic graft infection preparation, which is relevant to abdominal aortic and peripheral vascular graft infections. [12][13][14] These findings may not be applicable to the thoracic aorta because of the intrinsically different properties between the thoracic and abdominal aorta.…”
Section: Studies In Thoracic Aortic Graft Infections: the Development Of A Porcine Model And A Comparison Of Collagen-impregnated Dacron mentioning
confidence: 99%
“…This is in contrast to the established infrarenal aortic graft infection preparation, which is relevant to abdominal aortic and peripheral vascular graft infections. [12][13][14] These findings may not be applicable to the thoracic aorta because of the intrinsically different properties between the thoracic and abdominal aorta.…”
Section: Studies In Thoracic Aortic Graft Infections: the Development Of A Porcine Model And A Comparison Of Collagen-impregnated Dacron mentioning
confidence: 99%
“…The model of infrarenal aortic S. epidermidis polyester graft infection that we used mimics the clinical situation of late graft infection, resulting in a perigraft inflammatory process and anastomotic false aneurysm formation. 23,25,26 This model proba-bly differs from the clinical setting only in regard of the degree of contamination and the required time before the infection is established. 23,26 The study strain was a clinical isolate of S. epidermidis, which now causes an increasing number of vascular prosthetic graft infections.…”
Section: Discussionmentioning
confidence: 99%
“…23,25,26 This model proba-bly differs from the clinical setting only in regard of the degree of contamination and the required time before the infection is established. 23,26 The study strain was a clinical isolate of S. epidermidis, which now causes an increasing number of vascular prosthetic graft infections. 8 These organisms produce an extracellular matrix of glycocalyx that facilitates bacterial adherence and colonization of the graft material and protects the bacteria from host defenses and antibiotic penetration.…”
Section: Discussionmentioning
confidence: 99%
“…I-' Careful aseptic technique and pre-operative antibiotic prophylaxis minimizes the rate of infection but it still occurs up to a rate of 3.4%.3 Staphylococcus epidermidis is becoming an increasingly recognized problem in vascular surgery. Bandyk et al reported a 10 year series of 30 graft infections, 18 (60%) caused by Staph. epidermidis, though positive cultures were not obtained in three cases.4 They described Staph.…”
Section: Introductionmentioning
confidence: 99%